(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2024)
This research work aims at the design and development of a disruptive prototype for a Self-sufficient power plant (SSPP) prototype composed by cascaded disruptive power units (PUs) doing work by isothermal contraction-expansion processes. The innovative design integrates thermo-hydraulic actuators enabled to drive hydraulic pumps connected to a hydraulic motor-generator. The prototype’s cascaded PUs operates on a double closed processes-based isochoric-isothermal-isochoric-isothermal (VTVT) thermal cycle, enabled to do useful work by contraction and expansion of a thermal working fluid (TWF), which is notable for its high specific work output and high thermal efficiency. This is due to a disruptive cascaded heat recovering technique associated to a heat upgrading strategy. Among the most relevant Key Features are its self-sufficient operation modes that challenge traditional limitations of second-kind perpetual motion machines (PMMs) The expected capabilities on the basis of the consistency of empirical analysis are summarized as: - Design based on the optimal number of cascaded power units, - Efficient generation of useful mechanical work through expansion and contraction of the TWF, - High specific useful work (kJ/kg of TWF), such as helium, - Low ratio of actuator volume and weight to specific work. Preliminary tentative validation: The prototype design model was validated through case studies using air and helium as real TWFs. Empirical results demonstrate the SSPP’s exceptional performance under certain conditional restrictions. - The optimal SSPP completed with nine cascaded PUs each operating on a double-VTVT cycle per PU. - Helium: RIT value of 0.9 and 9 PUs coupled in cascade to give an SSI of 156.72and a SSEP yield of 922.23 kJ/kg.cy. - Air: RIT value of 0.9 and 9 PUs coupled in a shell to give an SSI of 27.41 and a SSEP production of 37.67 kJ/kg.cy. These findings highlight the prototype’s potential to significantly advance energy production efficiency and self-sufficiency in power generation systems.